1989
DOI: 10.1002/pssa.2211130214
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer investigation of the influence of Al(III) ions on the properties of mixed Fe(III)–Al(III) hydroxides and oxides

Abstract: Phase composition and components of mixed Fe(III)–Al(III) hydroxides and oxides obtained by ageing the hydroxides are examined mainly by Mössbauer spectroscopy over a wide range of the Al/Fe atomic ratio. The α‐(Fe1–cAlc)2O3 type oxide and the orthorhombic Al2O3, boehmite, are identified in the system studied. An analysis of Heff as a function of c indicates that the maximum value of c ranges from 0.31 to 0.33 regardless of the mixed oxide preparation method. An analysis of the recoil‐free fraction f′(T) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, it was found that the formation and crystallization of slightly soluble amorphous precipitates of hydroxides of transition and some other trivalent metals can not be fully described in terms of classical theory via the stage of dissolution [52,[69][70][71][72][73]. To explain the behavior of such precipitates, Buyanov and Krivoruchko developed a theory of formation of amorphous precipitates of slightly soluble hydroxides and oxides and their crystallization via the mechanism of "oriented accretion" [52].…”
Section: Tentative Mechanism Of Lanthanum Silicate Formation and Crysmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was found that the formation and crystallization of slightly soluble amorphous precipitates of hydroxides of transition and some other trivalent metals can not be fully described in terms of classical theory via the stage of dissolution [52,[69][70][71][72][73]. To explain the behavior of such precipitates, Buyanov and Krivoruchko developed a theory of formation of amorphous precipitates of slightly soluble hydroxides and oxides and their crystallization via the mechanism of "oriented accretion" [52].…”
Section: Tentative Mechanism Of Lanthanum Silicate Formation and Crysmentioning
confidence: 99%
“…The formation of primary 3-6 nm particles of individual hydroxides formed under great oversaturation with respect to the forming phase and their aggregates composed both from primary particles of different and the same chemical nature usually results in formation of corresponding oxides in the course of aging or thermal treatment of the residue [52,[71][72][73][74]. At the same time, the solid-state reaction between components of the mechanical mixture of silica and lanthana to form silicate with the apatite structure was shown to take place at temperatures exceeding 1000 ºɋ [75].…”
Section: Tentative Mechanism Of Lanthanum Silicate Formation and Crysmentioning
confidence: 99%